2016
DOI: 10.1016/j.ijrobp.2016.06.995
|View full text |Cite
|
Sign up to set email alerts
|

With or without Consolidation Chemotherapy for Clinical Responder to Definitive Concurrent Chemoradiation in Stage II-III Esophageal Squamous Cell Carcinoma

Abstract: Stereotactic body radiation therapy (SBRT) has become a treatment option for patients with unresectable focal hepatocellular carcinoma (HCC). Correlation between dose-volumetric parameters and late effects on liver function remain unclear. The purpose of this study is to analyze the factors predictive of liver dysfunction as a late effect after dynamic tumor-tracking (DTT) SBRT for HCC. Materials/Methods: Eligibility criteria in this study were as follows: (1) treated with DTT-SBRT for HCC; (2) received no add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We further analyzed the data eligible in our articles and found that the clinical features of 7 of those articles are similar in the CCT and the CCRT-alone groups. The clinical features in 4 articles were not detailed ( 9 , 18 , 23 , 24 ). The numbers of patients who did not accept CCT after CCRT reported by Koh, H. K. et al ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further analyzed the data eligible in our articles and found that the clinical features of 7 of those articles are similar in the CCT and the CCRT-alone groups. The clinical features in 4 articles were not detailed ( 9 , 18 , 23 , 24 ). The numbers of patients who did not accept CCT after CCRT reported by Koh, H. K. et al ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis, 1111 patients in 6 included articles demonstrated that CCT followed by CCRT can prolong PFS of EC patients (HR 0.61; 95% CI 0.44–0.84; p=0.003). Except for trials conducted by Chen, Y. et al ( 24 ). and Wu, S. X. et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation